Visibility of the Death Penalty in Indonesia: From Levy to Restoration - Adianto Adianto; Hariman Satria; Alasman Mpesau (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
In Indonesia, the death penalty is regulated in Article 10 letter a number 1 of the old Criminal Code and is placed as the main crime. The death penalty is a classic criminal law product which emphasizes that punishment must contain retribution or appropriate reward. Meanwhile, after the new Criminal Code was passed, the death penalty was made more flexible. There is a kind of paradigm shift in punishment from the old Criminal Code which was retaliatory in nature to the new Criminal Code which is restorative and rehabilitative in nature. The death penalty is made a special punishment and is threatened alternatively with other types of punishment, for example imprisonment for 20 years or life imprisonment. The death penalty can also be carried out through a probationary period.